Overview of the human papilloma virus: types and its treatment - Lolla, Siddhartha; Ilindra, Abhitha; Bajracharya (International Journal of Basic & Clinical Pharmacology, 2024)
The human papillomavirus (HPV) is the most prevalent sexually transmitted disease in the United States and one of the most common causes of sexually transmitted infections (STDs) globally. Warts are cutaneous and occasionally mucous lesions brought on by HPV, with 2-20% of elementary school students getting them. There are three types of warts: non-genital warts, flat warts, and plantar warts. Non-genital warts are hyperkeratotic, exophytic, dome-shaped papules or plaques commonly associated with HPV-1, 2, 4, 27, or 57. Flat warts appear as flesh-coloured, erythematous to brown, or hyperpigmented smooth papules with a flat top and a diameter of 2 to 5 mm. Plantar warts, also known as verrucae plantaris, are cutaneous lesions on the plantar aspect of the foot that result from a human papillomavirus infection of keratinocytes (HPV).Genital warts are transmitted through sexual contact, while autoinoculation and vertical transfer do occasionally happen. After engaging in sexual activity with an infected partner, about 70% of people experience anogenital warts. Treatment for HPV includes imiquimod cream formulations, photodynamic treatment (PDT), green tea, chemical cautery, fluorouracil cream, cryotherapy, and surgical treatment. Common warts are hyperkeratotic, exophytic, dome-shaped papules or plaques commonly found in fingers, dorsal surfaces of hands, knees, or elbows. Flat warts are flesh-coloured, erythematous to brown, or hyperpigmented smooth papules with a flat top and a diameter of 2 to 5 mm. Plantar warts are unique in their location and appearance, primarily affecting high-pressure locations on the palms and soles and are uniquely linked to HPV type 1.